The Future of Risk Mitigation in Procurement: Contractor Prequalification - Mazen Al-Sinan; Jassim Alsaleem (International Journal of Supply Chain Management, 2021)
-This paper discusses risk mitigation in procurement and how this could evolve over the next decade as a result of advances in Artificial Intelligence (AI) applications. The paper includes a literature review that covers contractors’ prequalification as a common measure for risk mitigation, a brief non-technical introduction to AI, and the previous research related to the application of AI in contractors’ prequalification. The paper expounds the current practice of contractor prequalification and reveals some of the current deficiencies in manual evaluation and the previously proposed AI models. Finally, the paper proposes a framework in which AI can assist risk mitigation in procurement.